Teaching-learning of the relevance of sustainability through an educational escape room designed for the field of economics and business - Paz Gil, Iria; Prado Roman, Alberto; Prado Roman, Miguel (Journal of Management and Business Education, 2023)
Sustainability is a key concept in business management. However, it is often confused with neighbouring terms, which hinders its correct understanding and, therefore, its correct application as a business model. In addition, there are no official curricula on the subject in the specific field of economics and business, so that current students do not receive the necessary training to be able to manage organisations, including companies, in a sustainable way in the near future. To fill this gap, a gamified didactic activity (an educational escape room) was designed with the main objective of familiarising participants with the concept of sustainability in this field. The results show a high level of satisfaction, as well as the suitability of the activity for training in the subject. The discussion concluded that although this tool, and gamification in general, is very interesting for transmitting new knowledge and consolidating previous knowledge (beyond the usual motivation), it requires a considerable investment of time and effort that the teacher, forced by multiple tasks, does not always have available.